Drosophila melanogaster as a Model System to Assess the Effect of Epstein-Barr Virus DNA on Inflammatory Gut Diseases - Madi, Joelle R.; Outa, Amani Al; Ghannam, Mirna; Hussein, Hadi M.; Shehab, Marwa; Hasan, Zeinab Al Kobra Haj; Fayad, Antoine Abou; Shirinian, Margret; Rahal, Elias A. (Frontiers in Immunology, 2021)
The Epstein-Barr virus (EBV) commonly infects humans and is highly associated with different types of cancers and autoimmune diseases. EBV has also been detected in inflamed gastrointestinal mucosa of patients suffering from prolonged inflammation of the digestive tract such as inflammatory bowel disease (IBD) with no clear role identified yet for EBV in the pathology of such diseases. Since we have previously reported immune-stimulating capabilities of EBV DNA in various models, in this study we investigated whether EBV DNA may play a role in exacerbating intestinal inflammation through innate immune and regeneration responses using the Drosophila melanogaster model. We have generated inflamed gastrointestinal tracts in adult fruit flies through the administration of dextran sodium sulfate (DSS), a sulfated polysaccharide that causes human ulcerative colitis- like pathologies due to its toxicity to intestinal cells. Intestinal damage induced by inflammation recruited plasmatocytes to the ileum in fly hindguts. EBV DNA aggravated inflammation by enhancing the immune deficiency (IMD) pathway as well as further increasing the cellular inflammatory responses manifested upon the administration of DSS. The study at hand proposes a possible immunostimulatory role of the viral DNA exerted specifically in the fly hindgut hence further developing our understanding of immune responses mounted against EBV DNA in the latter intestinal segment of the D. melanogaster gut. These findings suggest that EBV DNA may perpetuate proinflammatory processes initiated in an inflamed digestive system. Our findings indicate that D. melanogaster can serve as a model to further understand EBV-associated gastroinflammatory pathologies. Further studies employing mammalian models may validate the immunogenicity of EBV DNA in an IBD context and its role in exacerbating the disease through inflammatory mediators.